2017
DOI: 10.1021/acs.orglett.7b01292
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Asymmetric Total Synthesis of (+)-Vincadifformine, (−)-Quebrachamine, (+)-Aspidospermidine, (−)-Aspidospermine, (−)-Pyrifolidine, and Related Natural Products

Abstract: A uniformly strategic total synthesis of Aspidosperma alkaloids (+)-vincadifformine, (-)-quebrachamine, (+)-aspidospermidine, (-)-aspidospermine, (-)-pyrifolidine, and nine others from efficiently constructed tricyclic ketone 13 is reported. Highlights of these divergent and practical syntheses include (i) stereoselective intermolecular [4 + 2] cycloaddition to establish a C-E ring with one all-carbon quaternary stereocenter (C-5) and two bridged contiguous cis-stereocenters (C-12 and C-19), (ii) a Pd/C-cataly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 85 publications
0
42
0
Order By: Relevance
“…For example, vinblastine and vincrisitine were two well‐known drugs which were widely used in clinics for the treatment of various cancers . Combining their intriguing chemical structures and important biological activities, aspidosperma alkaloids attracted extensive attention from the synthetic community …”
Section: Natural Product Total Syntheses Via Diels‐ Alder Reaction Ofmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, vinblastine and vincrisitine were two well‐known drugs which were widely used in clinics for the treatment of various cancers . Combining their intriguing chemical structures and important biological activities, aspidosperma alkaloids attracted extensive attention from the synthetic community …”
Section: Natural Product Total Syntheses Via Diels‐ Alder Reaction Ofmentioning
confidence: 99%
“…Recently, Jiang and coworkers reported an efficient strategy to provide the enantiopure key tricyclic intermediate 378 in only eight steps (Scheme ), which could lead to a uniformly strategic total synthesis of fourteen Aspidosperma alkaloids, including (+)‐vincadifformine ( 380 ), (–)‐quebrachamine ( 381 ), (+)‐aspidospermidine ( 383a ), (–)‐aspidospermine ( 385b ), (–)‐pyrifolidine ( 385c ) and so on (Scheme ) [72a]. Jiang's strategy relied on the utilization of [4 + 2] reaction of 3‐ethyl‐5‐bromo‐2‐pyrone 365 with easily accessible chiral pentacyclic enamine 374 , providing hydroindolyl lactone 375 in 54% overall yield with good exo selecitivity ( exo / endo = 7: 1).…”
Section: Natural Product Total Syntheses Via Diels‐ Alder Reaction Ofmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxymethyl thiolactam cyclothialidine[1c] serves as a DNA gyrase inhibitor (Figure a). Moreover, thiolactam structural unit plays a vital role as an active functional group in organic chemical transformations, which has been applied for the formation of C—C bond and C=C bond as well as the construction of complex compounds such as jerantinine . However, limited methods have been developed for the synthesis of thiolactam due to the special structure with C=S bond (Figure b) .…”
Section: Background and Originality Contentmentioning
confidence: 99%
“…[4] Since the isolation and structure elucidation of vincadifformine,f our splendid syntheses in asymmetric versions have been achieved. [5] Each has its own feature in assembling the three-contiguous cis-stereocenters in the Er ing. In 2011, Pandey et al demonstrated ac ascade strategy to simultaneously construct C/E rings as well as the C12/C19 stereogenic centers in one pot.…”
mentioning
confidence: 99%